Policy Brief Effectiveness of Specific Nutrition Intervention Programs as Efforts to Prevent Stunting in Indonesia: Literature Review - Devy Kartika Sari; Anita Rahmiwati; Rostika Flora (Media Publikasi Promosi Kesehatan Indonesia (MPPKI), 2024)
Background: Stunting can hinder children's cognitive and physical development, cause decreased productivity, and it is feared that it can increase the risk of non-communicable diseases in adulthood such as diabetes, heart disease and other diseases. Therefore, early screening of children under five and immediate stunting intervention is very important. Objective: The purpose of this research analyze how the stunting prevention program is implemented in terms of Specific Nutrition Interventions. Method: This research looked for journals used in the literature review, journals used in the literature review were obtained through international journal provider databases such as Google Scholar and PubMed. Researchers wrote appropriate keywords, namely specific nutritional interventions, stunting, and Policy Brief. Results: Specific nutritional interventions are efforts to prevent and reduce nutritional problems directly. Specific nutritional interventions focus on adolescent women, pregnant women, breastfeeding mothers, and children under 2 years of age. Some of the literature examined shows that there are significant results from specific nutritional intervention programs. Conclusion: The implementation of this specific nutrition intervention program is very good, but there is still a need to improve the issue of good coordination and collaboration so that this specific nutrition intervention effort will have a good and sustainable impact in accordance with the world target regarding stunting prevention.